Boundary effects in finite size plasmonic crystals: focusing and routing of plasmonic beams for optical communications. (15th October 2015) - Benetou, M I; Bouillard, J-S; Segovia, P; Dickson, W; Thomsen, B C; Bayvel, P; Zayats, A V
Abstract: Plasmonic crystals, which consist of periodic arrangements of surface features at a metal–dielectric interface, allow the manipulation of optical information in the form of surface plasmon polaritons. Here we investigate the excitation and propagation of plasmonic beams in and around finite size plasmonic crystals at telecom wavelengths, highlighting the effects of the crystal boundary shape and illumination conditions. Significant differences in broad plasmonic beam generation by crystals of different shapes are demonstrated, while for narrow beams, the propagation from a crystal onto the smooth metal film is less sensitive to the crystal boundary shape. We show that by controlling the boundary shape, the size and the excitation beam parameters, directional control of propagating plasmonic modes and their behaviour such as angular beam splitting, focusing power and beam width can be efficiently achieved. This provides a promising route for robust and alignment-independent integration of plasmonic crystals with optical communication components.